Performance Accountability: Evaluation of Tourism Development in Indonesia - Nadia Azzahra; Abdul Jabbar; Irwan; Ahmad Mustanir; Muh. Tamrin; Kittisak Wongmahesak (JOURNAL OF GOVERNMENT SCIENCE, 2025)
This study aims to evaluate the Accountability of performance in the tourism sector of the Youth, Sports, and Tourism Office of Sidenreng Rappang Regency to achieve transparent and effective regional development targets. This study used the concept of accountability. The qualitative approach was used; data was collected through observation, interviews, and document analysis from June to July 2024, and the data was analysed using the NVivo 12 Plus application. The study results revealed that Disporapar had achieved most of the targets set in the 2023 Regional Apparatus Work Plan despite facing obstacles such as budget limitations and the quality of human resources. Priority programs such as improving human resource competence, developing tourist areas, and implementing various trainings have been successfully implemented and have a positive impact on increasing regional tourism attractiveness. Performance accountability assessments are based on five dimensions: legal and honesty, managerial, programmatic, policy, and financial. The findings show that program accountability is the most dominant dimension, with the success of most programs in achieving the set goals. Legal Accountability, honesty, and managerial Accountability also showed good performance, although there was room for improvement in financial reporting and transparency. In conclusion, the Accountability of the performance of the Sidenreng Rappang Regency Disporapar is quite good in achieving regional tourism development targets. However, improvements in several aspects are needed to ensure the effectiveness and efficiency of program implementation and the fulfillment of accountability obligations to the public.